Goal Orientation & Metacognitive Self-Regulation Students on Discourse Learning - Deasyanti, Deasyanti; Yudhistira, Santi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Corona Virus Disease 2019 (COVID-19) has impacted throughout all aspects of human life including education.Â Despite the previously applied distance education or e-learning in the conventional education, nowadays this instructional model became a newly common approach in education. Therefore, students have to make some adjustments in their learning approach in order to reach out their learning goals. Self-regulated learning (SRL) is a process of monitoring and controlling learning behaviors to achieve learning goals. One of the key factors that contribute to SRL is achievement goal orientation. The aim of this study is to find out the role of types of goal orientation towards metacognitive self-regulation. A total of 320 undergraduate students participated in this study. The findings showed that performance approach and performance avoidance were the significant predictors of metacognitive self-regulation. Studentsâ€™ preferences to performance goal-orientations were associated with the preliminary study findings that the new instructional model was related to decreased studentsâ€™ efficacy in learning and feelings of uncertainty to their academic achievement.